School Leadership Role in Nurturing a Sense of Responsibility in High Schools: A Comparative Study of Afghanistan and Indonesia - Kayen, Hazrat Shah; Wijayanti, Zaima Bunga; Delju, Zuliakha (Universitas Teuku Umar, 2023)
The development of a school and the readiness of teachers to teach with dedication, accountability, and enthusiasm depend significantly on leadership. Afghanistan has been a hub for educational advancement, and teachers' dedication and sense of accountability has been a key problem. The majority of Indonesia's educational administration and leadership challenges in schools, in contrast, have been resolved by professional leadership. Through a comparison of Indonesia and Afghanistan, the current study explored the function of school leadership in fostering a feeling of responsibility in teachers. They conducted interviews with school principals and teachers in both nations using a qualitative research design. The study's findings showed that school leaders were crucial in fostering a sense of responsibility at both research sites. Each nation has its own unique school principal practices and nurturing styles. In terms of fostering a sense of responsibility in school teachers, the leadership styles in both nations may be described as democratic in Indonesia and authoritative in Afghanistan as a result of the findings.